2008
DOI: 10.1177/0975156420080107
|View full text |Cite
|
Sign up to set email alerts
|

A study of Stress and Psychiatric Morbidity in the Central Industrial Security Force

Abstract: The Central Industrial Security Force (CISF) provides security cover to several of the Nation's vital industrial sectors and the CISF personnel are trained so as to meet expected and unexpected emergencies for varied periods of time.The present study is undertaken at the National industrial security Academy, NISA, Hyderabad with the objectives of assessing the psychiatric morbidity and the factors contributing to stress among the CISF personnel. A Random stratified sample of 500 subjects stratified to include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
5
1
Order By: Relevance
“…[ 26 27 ] Our study contrasts with the general population; industrial and armed force studies that had larger sample sizes; and the specific population studies on teachers, drivers, call-center workers, and industrial, security, and military workers which had smaller sample sizes. [ 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 ] The industrial, general population, and physician studies had referrals from the older age groups, whereas studies on military personnel, executives, and call-center workers had younger age groups as compared to our study. [ 28 29 30 31 32 33 34 35 37 40 41 42 43 44 45 46 ] Most of the foreign studies did not report about socioeconomic data.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…[ 26 27 ] Our study contrasts with the general population; industrial and armed force studies that had larger sample sizes; and the specific population studies on teachers, drivers, call-center workers, and industrial, security, and military workers which had smaller sample sizes. [ 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 ] The industrial, general population, and physician studies had referrals from the older age groups, whereas studies on military personnel, executives, and call-center workers had younger age groups as compared to our study. [ 28 29 30 31 32 33 34 35 37 40 41 42 43 44 45 46 ] Most of the foreign studies did not report about socioeconomic data.…”
Section: Discussioncontrasting
confidence: 54%
“…[ 27 28 29 30 34 ] The diagnostic categories of our study compare with the hospital-based Indian studies but not with the community-based studies, industrial studies, and the special population-based studies done on teachers, physicians, executives, call-center workers, and drivers. [ 3 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 ] Studies on executive, call-center, and social workers found only minor psychiatric disorders. [ 25 34 39 ] Studies on armed force personnel had more substance-use disorders and neurotic disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 10 11 ] In a study of Central Industrial Security Force (CISF) personnel at National Industrial Security Academy, Hyderabad, prevalence of psychiatric morbidity was reported to be 28.8% with the majority suffering from generalized anxiety disorder and major depressive disorders. [ 12 ]…”
mentioning
confidence: 99%
“…[8] A recent study conducted on Central Industrial Security Force has revealed that personnel posted in stressful areas and the rank of constables perceived more stress and psychiatric morbidity compared with those posted in nonstressful areas. [16] A recent study on police personnel showed that the relationship between work characteristics and mental health outcomes was mediated by perceived stress. [17] Job satisfaction mediated the relationship between positive work characteristics and depression.…”
Section: Introductionmentioning
confidence: 99%